2019
DOI: 10.5114/aoms.2018.75818
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide B and neuropeptide W as new serum predictors of nutritional status and of clinical outcomes in pediatric patients with type 1 diabetes mellitus treated with the use of pens or insulin pumps

Abstract: Introduction The aim of our study was to determine the relationship between neuropeptide B (NPB), neuropeptide W (NPW), nutritional and antioxidant status and selected fat- and bone-derived factors in type 1 diabetes mellitus (T1DM) treated using pens (T1DM pen group) or insulin pumps (T1DM pump group) in order to investigate the potential role of NPB and NPW in the clinical outcomes of T1DM. Material and methods Fifty-eight patients with T1DM and twenty-five healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…We found that nPB and its receptor are present in rat adipocytes (11) where nPB stimulates lipolysis and suppresses leptin expression, and secretion (11). others have reported that nPB serum level is upregulated in humans who suffer from anorexia nervosa (12), while it is reduced in type 1 diabetic patients (13). overall, these results collectively indicate that the nPB/nPBW1 system is involved in controlling body weight and energy homeostasis and its alternation may contribute to obesity.…”
Section: Introductionsupporting
confidence: 66%
“…We found that nPB and its receptor are present in rat adipocytes (11) where nPB stimulates lipolysis and suppresses leptin expression, and secretion (11). others have reported that nPB serum level is upregulated in humans who suffer from anorexia nervosa (12), while it is reduced in type 1 diabetic patients (13). overall, these results collectively indicate that the nPB/nPBW1 system is involved in controlling body weight and energy homeostasis and its alternation may contribute to obesity.…”
Section: Introductionsupporting
confidence: 66%
“…Enriched genes such as CCR2 [56], CCL19 [57], CX3CL1 [58], CXCL12 [59], IL20 [60], epidermal growth factor receptor (EGFR) [61], ERBB3 [62], adrenomedullin (ADM) [63], SCUBE1 [64], LMAN1L [65] and EGFL7 [66] were responsible for pathogenesis of CAD. Enriched genes such as CXCL6 [67], BMP7 [68], RXFP2 [69], BRS3 [70], FFAR3 [71], neuropeptide B (NPB) [72], SPON2 [73], FCN3 [74], REG3A [75] and ornithine carbamoyltransferase (OTC) [76] were culpable for pathogenesis of diabetes, but these genes may be involved in development of CAD. Enriched genes such as COL18A1 [77], cortistatin (CORT) [78], guanine nucleotide binding protein (G protein) [79] and MUC2 [80] were involved in development of obesity, but these genes may be associated with pathogenesis of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as CCR2 [61], CCL19 [62], CX3CL1 [63], CXCL12 [64], IL20 [65], epidermal growth factor receptor (EGFR) [66], ERBB3 [67], adrenomedullin (ADM) [68], SCUBE1 [69], LMAN1L [70] and EGFL7 [71] were responsible for pathogenesis of CAD. Genes such as CXCL6 [72], BMP7 [73], RXFP2 [74], BRS3 [75], FFAR3 [76], neuropeptide B (NPB) [77], SPON2 [78], FCN3 [79], REG3A [80] and ornithine carbamoyltransferase (OTC) [81] were culpable for pathogenesis of diabetes, but these genes might be involved in development of CAD. Genes such as COL18A1 [82], cortistatin (CORT) [83], guanine nucleotide binding protein (G protein) [84] and MUC2 [85] were involved in development of obesity, but these genes might be associated with pathogenesis of CAD.…”
Section: Discussionmentioning
confidence: 99%